Effectiveness of Instructional School Leadership in Public Secondary Schools in Buea - Mbua, Emile Monono (American Journal of Leadership and Governance, 2023)
Purpose: The purpose of this study was to investigate the effectiveness of instructional school leadership in public secondary schools in Buea. Methodology: This study employed a non-experimental descriptive-correlation research design. The sample included 450 respondents (50 principals, vice principals and 400 teachers). Forty (40) teachers from each school were obtained using the stratified and simple random sampling methods, and the principals and vice principals of the sampled schools were automatically used as respondents. This research study utilized the Principal Instructional Management Rating Scale (PIMRS) survey for teachers to evaluate the public secondary school principal's instructional leadership capacity. The data collected were analyzed by calculating the percentage, Mean and Pearson r Correlation. Findings: The study found a significant relationship between teacher's perceptions of principals' instructional leadership towards defining school mission (r-cal=3.444, p<0.05). There was significant relationship between teachers' perception of principals instructional leadership towards managing instructional program (r -cal=3.321, p<0.05). There was a significant relationship between teachers' perception of principals instructional leadership towards developing school-learning climate (r-cal=3.134, p<0.05). Recommendation: The study recommend that principals should develop a comprehensive mission that addresses every facet of the school if they are to perform an effective instructional leadership function.